Moehlman's Bottoms, Riley County - Brummett, Katie (Kansas State University, The Chapman Center for Rural Studies, 2011)
This paper chronicles the story of Henry Moehlman and the development of Moehlman Bottoms in Riley County, Kansas. Includes effects of natural disasters, early Kansas rural education, historical photos, and present day maps and pictures of Moehlman Bottoms.
Katie Brummett, “Moehlman's Bottoms, Riley County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/16.
Keywords: Ft. Leavenworth- Ft. Riley Military Road; Henry Moehlman; Kansas River; Riley County; Prussia; Tuttle Creek Dam